Efeitos da invasão do mexilhão-dourado (Limnoperna fortunei) na dinâmica populacional de organismos fitoplanctônicos - Fabiano Alcísio e Silva (2018)
Considered as one of the most aggressive freshwater invasive species, the golden mussel (Limnoperna fortunei) has been intensively studied and its impacts widely discussed in the scientific literature. Additionally, the aquatic environments have suffered impacts from different anthropic activities, going against the increasing global necessity for high quality water. In recent years, the golden mussel invasive process has accelerated in Brazil, and it currently reaches different watersheds with scenic, economic and ecological importance. The impacts caused by the bivalve in these invaded environments are still quite discussed and often contradictory. The impacts of the golden mussel introduction on the trophic chain of invaded environments present several contradictory points of view in the literature. The temporal and spatial variations, and the intrinsic characteristics of each particular environment, are the main causes of these divergences. In this sense, this study sought to contemplate different temporal and spatial scales, covering studies in the laboratory, in mesocosmos and in the field, in addition to different time scales, which varied from a few days to two years. The first phase of the study was carried out in a battery of 11-day laboratory experiments, under controlled conditions, when the animals were fed on a cyanobacterium and a green alga. Then, twelve-day mesocosmic scale experiments were performed in a reservoir invaded by the bivalve, using the reservoir water and the local plankton community. Finally, a two years’ monitoring sampling was followed in the field at monthly intervals in a reservoir recently invaded by the golden mussel. The results, both experimental and from field observation, revealed the high capacity of golden mussel to alter the physical and chemical properties of the water. In particular, we observed increased light penetration into the water and increased concentration of dissolved nutrients such as ammonium and phosphorus. In addition, this study confirms that the presence of the golden mussel, even on a few days scale, would be able to modify the structure of the phytoplankton community, favoring some groups and harming others. The results, therefore, corroborate the main hypotheses raised here, which proposed that the introduction of the golden mussel could have an effect on the trophic structure of the invaded environments, through selective pressure by filtration and greater accumulation of nutrients in the water, consequence of its metabolic activity. Among the favored species, Microcystis aeruginosa, a cyanobacterium able to form blooms and to produce toxins, had its density increased in the laboratory experiments. The results presented in this PhD thesis can therefore serve as the basis for the development of tools with the purpose of managing, controlling and mitigating the impacts caused by the golden mussel in the environments.